Meningkatkan literasi anak-anak desa Barabali melalui program pojok baca masyarakat - Raehanah Raehanah; Ahmad Fahrul Riadi (Participative Journal: Jurnal Pengabdian Pada Masyarakat, 2023)
West nusa tenggara is one of the three provinces with the lowest Proficiency Dimension Index. The Village of Barabali as one of the areas in Central Lombok has the same problem. The low level of community literacy is due to the low level of The community education as well. The daily habits of people who don’t like to read makes them lack of literacy. Children and adolescents prefer to use the internet for entertainment rather than reading science. Therefore, efforts such a community services are needed to increase the literacy level from an early age, namely childhood. This service is carried out in three stages, which is observation, outreach, and implementation. Observation is taken to determine the condition of the community related to literacy levels and supporting infrastructure. Socialization campaign aims to introduce the community regarding the program being carried out and explain the importance of reading science in life. The implementation phase includes activities such as reading stories and fairy tales, drawing, making origami and others. Based on the results of the activities, public reading corners can foster children's interest on books. The reactivation of the reading room in Barabali Village made the children enthusiastic about it